Sustainability: an investigation of the attitude and behavior of management students - Melo, Danielle Nunes Bezerra de; Romero, Claudia Buhamra Abreu; Reinado, Hugo Osvaldo Acosta; Abreu, Cristiane Buhamra (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
Concern about the environment is a recurring theme on the world stage, making the planet's sustainability a focus of discussions among governments, organizations and society. To meet the new demands of the market, organizational managers are being challenged to adopt sustainable corporate strategies that stimulate the financial growth of companies, while assuming the socio-environmental responsibility that they are entitled to. Thinking about the future managers, this work aims to analyze the environmental attitude and behavior of students of the undergraduate program in Administration. Classified as descriptive and quantitative, as well as carried out with 269 students of the Administration program of the Federal University of Ceará – UFC, the study suggests the students have attitudes prone to sustainability, but their behaviors are not favorable, being classified as less conscious about the importance of their actions for the environment preservation.